2008
DOI: 10.1590/s1807-59322008000500014
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Leptin, Adiponectin Levels and Paraoxonase Activity with Metabolic and Cardiovascular Risk Factors in Females Treated with Psychiatric Drugs

Abstract: Ozenoglu A, Balci H, Ugurlu S, Caglar E, Uzun H, Sarkis C et al. The relationships of leptin, adiponectin levels and paraoxonase activity with metabolic and cardiovascular risk factors in females treated with psychiatric drugs. Clinics. 2008; 63(5):651-60. OBJECTIVES:The aim of this study was to investigate serum leptin, adiponectin and paraoxonase1 levels in adult females receiving pharmacotherapy for various psychiatric disorders. METHODS:The study group consisted of 32 obese females (mean age 40.53 ± 11.00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…Although we didn’t have a control group, the average activity of the enzyme we found in this study was not very different from the activity found by other studies in women without endometriosis (183.7 ± 22.3 U/l in 40 women with no endometriosis in the study of Verit et al, 2008 [10]; 258.29 ± 101.95 U/l in 22 adult females with no endocrine or metabolic disorders or history of drug use in the study of Ozenoglu et al, 2008 [28]; and 240 ± 144 U/l in 200 individual, both men and women, from blood bank serum samples in a study performed by Davis et al, 2009 [29]). Besides, in our study the patients were diagnosed with endometriosis by laparoscopy/laparotomy, and classified according to the American Society for Reproductive Medicine [26] with histological confirmation of the disease, which gives a more accurate diagnosis of the stage of the endometriosis in comparison with visual confirmation alone.…”
Section: Discussioncontrasting
confidence: 69%
“…Although we didn’t have a control group, the average activity of the enzyme we found in this study was not very different from the activity found by other studies in women without endometriosis (183.7 ± 22.3 U/l in 40 women with no endometriosis in the study of Verit et al, 2008 [10]; 258.29 ± 101.95 U/l in 22 adult females with no endocrine or metabolic disorders or history of drug use in the study of Ozenoglu et al, 2008 [28]; and 240 ± 144 U/l in 200 individual, both men and women, from blood bank serum samples in a study performed by Davis et al, 2009 [29]). Besides, in our study the patients were diagnosed with endometriosis by laparoscopy/laparotomy, and classified according to the American Society for Reproductive Medicine [26] with histological confirmation of the disease, which gives a more accurate diagnosis of the stage of the endometriosis in comparison with visual confirmation alone.…”
Section: Discussioncontrasting
confidence: 69%
“…Adipose tissue is a complex, essential, and highly active metabolic and endocrine organ (Kershaw & Flier, 2004) who communicates with the central nervous system (Costa et al, 2011). In addition to energy storage, also regulate energy metabolism via secreting adipokines into the circulation (Ozenoglu et al, 2008). Adipokines is bioactive peptides, which act at both the local and systemic level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in energy storage, adipose tissue also secretes various biologically active adipokines such as leptin, and the anti-inflammatory and antiatherosclerotic adiponectin (25). Previous studies have shown correlations between the activity of PON1, and levels of adiponectin and leptin (3,(26)(27)(28). Moreover, the effect of inflammatory cytokines such as tumor necrosis factor-α, whose levels are higher in plasma of obese patients (29), deserves of future studies because they negatively affect PON1 synthesis (30).…”
Section: Discussionmentioning
confidence: 99%